Rezim Harta Perkawinan dalam Hukum Islam: Analisis Perbandingan Mazhab dan Integrasinya ke dalam Tata Kelola Ekonomi Islam Modern - Ahmad Mubarak; Nahdia Nazmi; Muhamad Rahmani Abduh; Nurul Azkia; Novy Listiana; Iqnaul Umam Ashidiqi (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The economic transformation of contemporary Muslim families has significantly reshaped the ownership, management, and distribution of property within marriage. This development has generated legal tension where classical fiqh, which generally upholds separate ownership between spouses, confronts the realities of dual-income households, women’s economic contribution, and increasing state intervention in the pursuit of family justice. Marital property must therefore be understood not merely as a matter of private law, but as an issue located at the intersection of Islamic family law, Islamic economic law, comparative madhhab analysis, and state legal governance. This article aims to analyse the normative construction of marital property regimes across the Sunni madhhabs, examine their integration into modern state law, and formulate a more just and context-sensitive conceptual model. The study employs a qualitative legal research design based on a doctrinal-comparative approach, complemented by a limited socio-legal perspective. Data were collected through systematic library research and documentary legal research, and analysed through qualitative content analysis, comparative legal analysis, and normative-constructive analysis. The findings show that classical Islamic law does not recognise the automatic fusion of property by virtue of marriage, yet it provides normative resources through milkiyyah, shirkah, ‘urf, nafaqah, and maqāṣid al-sharīʿah to acknowledge entitlements arising from both direct and indirect contribution. The central problem lies not in the absence of Islamic norms, but in the weak translation of those norms into fair adjudicative methods and state policy. This article proposes a maqāṣid-based relational marital property regime that balances individual ownership, economic and domestic contribution, the social function of family assets, and equitable adjustment. It concludes that reform of marital property law should move towards interpretations that are more responsive to contribution, child protection, and the economic governance of modern Muslim families.